The use of balustrades on bridges in the light of applicable regulations - Michał Żochowski (Przegląd Komunikacyjny)
Abstract: The author presented the legal status in relation to the use of balustrades on bridges. The analysis presented regulations on technical conditions on bridges and regulations on occupational health and safety. The article attempts to carry out the analysis in such a way that the conclusions are universal and can be applied to all types of objects. It has been shown that the balustrades are an element which protects against falling from a height. This type of collective protection elements should be used when there is a risk of falling from a height.